2009
DOI: 10.5014/ajot.63.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Obesity Among African-American Women in Omaha

Abstract: Obesity is a health disparity related to environmental, social, and physical health issues, including ethnicity, education, and gender. The purpose of this study was to examine the relationship among obesity, age, education, and socioeconomic status and the relationship between obesity and depression among African-American women living in Omaha, Nebraska. A convenience sample of 378 African-American women completed the African-American Female Health Survey, which included the Center for Epidemiologic Studies D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Depressive symptoms in our study were positively correlated with prepregnancy BMI. This positive relationship was also found in previous studies that included either adult nonpregnant women (Blanchard, 2009;Keddie, 2011;Pan et al, 2012), postpartum women (LaCoursiere et al, 2010), or pregnant women (Bodnar et al, 2009). One previous study, however, did not find such a relationship when prepregnancy BMI was collected 4 months after delivery (Carter et al, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…Depressive symptoms in our study were positively correlated with prepregnancy BMI. This positive relationship was also found in previous studies that included either adult nonpregnant women (Blanchard, 2009;Keddie, 2011;Pan et al, 2012), postpartum women (LaCoursiere et al, 2010), or pregnant women (Bodnar et al, 2009). One previous study, however, did not find such a relationship when prepregnancy BMI was collected 4 months after delivery (Carter et al, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…Studies exploring the nutritional values for foods consumed by AAW focus on either excessive or insufficient nutrient intake, such as calcium found in dairy foods, minerals, and vitamins from fruits and vegetables, and carbohydrates and saturated fats that disproportionately influence disease outcomes among AAW (Blanchard, 2009;Kannan et al, 2010;Sharma et al, 2009). Lacking are studies to determine where, what and how AAW spend funds for food allocation.…”
Section: Nutrition and Food Preparationmentioning
confidence: 99%
“…Consequently, many AAW omit calcium rich dairy foods, resulting in dietary calcium levels lower than the current RDA of 1,000 to 1,200 milligram (mg) daily for adults 19 years and older (USDA, 2005;. Such a diet reduces the potential benefits gained from consuming three to four daily servings of the low-fat dairy foods (Blanchard, 2009;Kannan et al, 2010;Teegarden, 2003;Wooten & Price, 2004) that have been found to reduce chronic diseases (i.e., obesity, hypertension, diabetes, atherosclerosis, and osteoporosis) affecting AAW, promote weight loss in obese persons (Blanchard, 2009;Wooten & Price, 2004) and increase the long-term risk for lower BMD levels at midlife. In addition, Houston et al (2005) reported that among a group of AA and EA women, dairy, fruit, and vegetable intakes were inversely associated with lower extremities limitation and impaired ADL, among AAW.…”
Section: Nutrition and Food Preparationmentioning
confidence: 99%
See 2 more Smart Citations